SIMULASI KARIES GIGI DENGAN INHIBISI EKSTRAK DAUN SIRIH (Piper betle L.) BERDASAR ANALISA ION KALSIUM - Ni Made Listiani; Dwi Warna Aju Fatmawati; Sri Lestari (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2011)
Caries of tooth occurs when there is interaction between four etiology factors, such us : tooth surface, substrat, microorganism, and time. The substrat will fermented by microorganism and produce acidity. This acidity caused some components of tooth released, called demineralization. One of the tooth major component is calcium. One way to prevent demineralization is inhibit the activity of microorganism. One of traditional plant that can be use is Piper betle L. The purpose of the study was to investigate the efficiency of Piper betle L. extract to inhibit calsium ion of tooth release. Twelve maxillary first premolars were divided into three groups. The first group (A) was immersed in synthetic saliva and S. mutans, the second group (B) in synthetic saliva, sucrose and S. mutans, and the third group (C) in synthetic saliva, sucrose, S. mutans and Piper betle L extract, for 24 hours each. To identify the calcium ion oftooth release into the immersion media, each sample was tested by Atomic Absorption Spectrophotometry. The results show that group C has the lowest mean. It was concluded that Piper betle L. is efficient to inhibit the calsium ion of tooth release.